DAKWAH TRANSFORMATIF MOHAMMAD NATSIR - al-Asy’ari, M. Khoirul Hadi (WALISONGO, 2014)
Daâwa is probably the best effort to spread Islam. In the context of Indonesia, somany figures engaged in Islamic daâwa. One of them is Mohammad Natsir whoimplemented transformative Islamic daâwa in of his life times. Applying qualitativeresearch with historical approach, both on his life history and his writings, it wasfound that transformative efforts on the dakwah movement implemented byMohammad Natsir was based on the principles of verbalic deeds, actualization ofIslam in a factual actions, and good personily. The principles had been implementedby doing organizational breakthrough toward the community. Applyingthis strategy made the daâwa movement infiltrated toward all levels of society.Nowadays it was showed that the organization set up by Mohammad Natsirdeveloped well and support the religiousity among Indonesian society.***Dakwah adalah salah satu upaya untuk menyebarkan agama Islam. Dalamkonteks Indonesia, banyak sekali tokoh yang bergerak dalam bidang dakwah.Salah satunya adalah Mohammad Natsir. Mohammad Natsir melakukan dakwahtranformatif pada zamannya. Dengan menggunakan penelitian kualitatif, denganpendekatan sejarah, baik melalui sejarah kehidupan maupun karyanya ditemukanbahwa upaya transformatif dalam gerakan dakwah yang dilakukan olehMohammad Natsir didasarkan pada prinsip amal perbuatan lisan, aktualisasiajaran Islam dengan karya nyata, dan kepribadian terpuji. Upaya yang dilakukannyaadalah melakukan gebrakan organisatoris. Implementasi dakwah MohammadNatsir melalui gerakan organisasional telah terbukti menyebar di seluruhwilayah Indonesia dan membentuk keberagamaan Islam di Indonesia.Keywords: dakwah, dakwah transformatif, Mohammad Natsir,Dewan Dakwah Islamiyyah Indonesia